Biaxial fatigue tests and crack paths for AISI 304L stainless steel - V. Chaves; C. Madrigal; A. Navarro (Fracture and Structural Integrity)
AISI 304L stainless steel specimens have been tested in fatigue. The tests were axial, torsional and in-phase biaxial, all of them under load control and R=-1. The S-N curves were built following the ASTM E739 standard and the method of maximum likelihood proposed by Bettinelli. The fatigue limits of the biaxial tests were represented in axes ?-?. The elliptical quadrant, appropriate for ductile materials, and the elliptical arc, appropriate for fragile materials, were included in the graph. The experimental values were better fitted with an elliptical quadrant, despite the ratio between the pure torsion and tension fatigue limits, ?FL/?FL, is 0.91, close to 1, which is a typical value for fragile materials. The crack direction along the surface has been analyzed by using a microscope, with especial attention to the crack initiation zones. The crack direction during the Stage I has been compared with theoretical models.